Storage and Viability of Hevea Seeds - Mohamad Husin, Sakhibun (1981)
Observation on the flowering habit, fruit set and seed development of Hevea brasiliensis Muell Arg. was carried out on Clone RRIM 600. Flowering appeared to be more frequent under exposed, sparsely planted conditions and on flat terrain. Morphological and structural changes continued from fruit set until dehiscence. The fruits ripened and dehisced from 23 to 24 weeks after anthesis. Seed viability was highest before fruit dehiscence. At this stage the dry weight of the fruit and the seed were highest and their moisture content was lowest. Germination percentage of seeds of different maturity and of different periods of stor.age was significantly different. Seeds extracted from fruit 19 and 20 weeks after anthesis gave only 39% and 52% germination respectively. Dry weight, percentage germination and seedling vigour increased in seeds that were more mature. Seeds from fruits 22 weeks after anthesis gave the highest germination percentage, but storage life was longest for seeds from 21 week old fruits . Fruit colour can be used for estimating seed maturity during fruit · harvest. Studies were carried out to evaluate the combination effect of three different storage temperatures and chemtcal treatments on the viability of seeds of Hevea. Chilling at 50C and addition of polyethylene glycol (PEG 1500), sodium chloride (0.08 molar) and abscisic acid (25 ppm) produced moderate response in prolonging the seed life in storage. All treatments in air-conditioned storage at 210e, except polyethylene glycol, gave poor results.